In search of a narrative for Southern providers: the challenge of the emerging economies to the development cooperation agenda - Gerardo Bracho (Deutsches Institut für Entwicklungspolitik (DIE), 2015)
The advent of the so-called Southern providers has profoundly disrupted the logic of the development cooperation agenda, based on a clear division between developed and developing, donor and recipient countries. During the post-war era, this agenda was informed by two paradigms: North-South (Truman's “point 4” in 1949) and South-South (Bandung in 1955). Neither, however, can make sense of this new third actor, the Southern provider: an emerging power that has become – or is on its way to becoming – an important donor of development assistance but which, at the same time, remains firmly rooted in the South, confronted with typical development challenges and retaining the right to receive official development assistance. Which countries should be included in this new constituency in the making? What codes and practices should they adopt? Most importantly, what (if any) responsibilities should they take on vis-à-vis other poorer Southern countries left behind by globalisation? And finally, where should these inquiries be legitimately settled and by whom? Addressing these questions is crucial to incorporating the Southern providers constructively into the evolving aid architecture and the post-2015 development agenda. So far, there are no consensual answers but rather confusing and sometimes heated debates on these issues in multilateral fora, academia and cooperation agencies. Indeed, the battle to create a new narrative and a legitimate home for the Southern provider, which has gone on for more than a decade, has taken a bumpy road, both due to the mixed incentives that the different stakeholders face in this venture as well as the persistence of the North-South and South-South paradigms, which refuse to adapt to the times. The arrival of the Southern providers has brought more resources to the aid agenda and much needed intra-donor competition. But the lack of clear answers and agreements on their roles and responsibilities has also had adverse consequences. It has compromised the practices and narrative of the traditional donors at the expense of the neediest countries. It has also contributed to perpetuating a world divided into blocks, precisely when collective action is more necessary than ever. Mexico, as an actor that has both South and North affiliations, has had a mediating role in this agenda and should continue to do so. This essay is intended to document some of the main episodes of the battle to generate a narrative for the Southern provider. It starts with a brief historical presentation of the North-South and South-South cooperation traditions. Next, the factors that destabilised this dual tradition and precipitated the current crisis are discussed – in particular, the role of the emerging Southern donor is examined. Then the slow and troubled gestation of a narrative that seeks to make sense of this new actor in the development cooperation agenda is described in more detail, as well as the efforts that have been made to give these actors an institutional home. Finally, reflections are offered on the negative impact of the stagnation of these processes on the emerging post-2015 development cooperation agenda and on the constructive role that Mexico has played (and in this author's opinion, should continue to play). The paper concludes by situating the challenge of the Southern providers in the larger context of an increasingly multipolar world.
Keywords: 330; Aufstrebende Mächte; Entwicklungsfinanzierung und öffentliche Finanzen